“Conditional scholarships” for HIV/AIDS health workers: educating and retaining the workforce to provide antiretroviral treatment in sub-Saharan Africa - Bärnighausen, Till; Bloom, David E. (Social science & medicine, 2009)
Without large increases in the number of health workers to treat HIV/AIDS (HAHW) many countries in sub-Saharan Africa will be unable to achieve universal coverage with antiretroviral treatment (ART), leading to large numbers of avoidable deaths among people living with HIV/AIDS. We conduct a cost-benefit analysis of a health care education scholarship that is conditional on the recipient committing to work for several years after graduation delivering ART in sub-Saharan Africa. Such a scholarship could address two of the main reasons for the low numbers of health workers in sub-Saharan Africa: low education rates and high emigration rates. We use Markov Monte Carlo microsimulation to estimate the expected net present value (eNPV) of “conditional scholarships” in sub-Saharan Africa. The scholarships are highly eNPV-positive under a wide range of assumptions. Conditional scholarships for a HAHW team sufficient to provide ART for 500 patients have an eNPV of 1.24 million year-2000 US dollars, assuming that the scholarship recipients are in addition to the health workers who would have been educated without scholarships and that the scholarships reduce annual HAHW emigration probabilities from 15% to 5% for five years. The eNPV of the education effect of the scholarships is larger than eNPV of the migration effect. Policy makers should consider implementing “conditional scholarships” for HAHW, especially in countries where health worker education capacity is currently underutilized or can be rapidly expanded.